Manajemen Perawatan Kebersihan Diri dan Pengobatan Masyarakat untuk Mewujudkan Desa Sadar Kebiasaan Hidup Baru (New normal) di Masa Pandemi Covid 19 di Desa Pedawang Kabupaten Pekalongan - I Irnawati; Benny Arief Sulistyanto (Prosiding University Research Colloquium, 2020)
Community service activities had a purpose to make the community have a proficiency in: (1) to improve knowledge about personal hygiene and covid 19 prevention protocols to realize newnormal habits aware village in the covid-19 pandemic; (2) awareness of the disease; (3) awareness of seeking treatment for disease. The target audience for these activities were communities in pedawang village in Pekalongan District were 67 participants. This activity was preceded by conducting an analysis of the needs of through interviews and surveys of public health issues. The implementation of the activities carried out was health education about personal hygiene and covid 19 prevention protocols, medical examinations by doctors, and blood tests. Forms of activity are designed using health education strategies to ensure participants’ knowledge in treatment disease and preventing spread of covid 19 can be mastered well. Results from health education showed 66% of participants had good knowledge about personal hygiene and covid 19 prevention protocols (more than 70% of participants' answers were correct). In conclusion the level of knowledge of the community is quite good. The advice is to provide health education with small groups.